(untitled) (PERcursos Linguísticos, 2024)
ABSTRACT: In this article, we seek to address the way in which our cultural lenses, based on a matrix of power, create abysmal lines when considering autism spectrum disorder, especially the issue of “disability. To this end, three aspects will be highlighted - decoloniality, ASD and Vygotsky’s historical-cultural psychology to address the complexity of the discussion. We emphasize the need for a critical epistemology that questions power relations and promotes the inclusion of historically excluded perspectives. We emphasize the need to fight for the inclusion of people with autism, whose voices and experiences are often ignored or devalued in discussions about social policies, education and employability. We also address the need to face the challenges associated with ASD that require collective, interdisciplinary and continued efforts, which transcend the barriers of pathologization and open paths for the full participation and recognition of people with autism in all areas of everyday life. KEYWORDS: Decoloniality. Autism Spectrum Disorder. Applied Linguistics.